Morphological and Compositional Analysis of Electrodeposited Indium (III) Sulfide (In2S3) Films. Issue 7 (1st January 2015) - Mughal, Maqsood Ali; Engelken, Robert; Newell, M. Jason; Vangilder, Joshua; Thapa, Shyam; Wood, Kayla; Carroll, B. Ross; Johnson, J. Bruce
Abstract : Within the last few years, there has been notable progress in understanding the growth mechanisms of semiconductor thin films for photovoltaic (PV) applications. Electrodeposition continues to be a complex deposition technique that can lead to regions of low quality (for example, cracks) in films. Such cracks can form porous zones on the substrate and diminish the heterojunction interface quality of a PV cell. In this paper, electrodeposition of In2 S3 films was systematically and quantitatively investigated by varying electrodeposition parameters including bath composition, current density, deposition time, and deposition temperature. Their effects upon the morphology, composition, and film growth mechanism were studied with the help of scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and digital imaging analysis (using fracture and buckling analysis software). In addition, the effect of different annealing treatments (200°C, 300°C, and 400°C in air) and coated glass-substrates (Mo, ITO, and FTO) upon the properties of the In2 S3 films was analyzed. Furthermore, the Taguchi/Design of Experiments (DOE) Method was used to determine the optimal electrodeposition parameters in order to improve the properties.